A retrospective cohort study of the association between midwifery experience and perinatal mortality. Issue 1 (20th October 2015) - Lawton, Beverley; Filoche, Sara; Geller, Stacie E.; Garrett, Sue; Stanley, James
Abstract: Objective: To determine whether experience of midwife‐only and nurse‐midwife lead maternity carers (LMCs) is related to perinatal mortality. Methods: In a retrospective analysis, routinely collected data were obtained for all pregnancies resulting in live births (or stillbirth at ≥ 20 weeks or weighing > 400 g) in New Zealand in 2005–2009. An anonymized dataset of date of midwife registration was used. The main outcome measure was perinatal mortality (fetal deaths and neonatal deaths ≤ 27 days). Results: Among 233 215 eligible births, 84 043 were linked to a midwife‐only LMC and 150 172 to a nurse‐midwife LMC. Among pregnancies with midwife‐only LMCs, perinatal mortality was higher when the midwife had less than 1 year of experience than when the midwife had 5–9 years' experience (rate ratio 1.33; 95% confidence interval 1.02–1.73), an absolute difference of two additional deaths per 1000 births. There was a decreasing rate of perinatal mortality with increasing experience ( P = 0.031). Perinatal mortality rates did not differ by experience in the nurse‐midwife group. Conclusion: Pregnancies cared for by early‐career (< 1 year) midwife‐only LMCs were associated with a 33% increase in perinatal mortality. No association between experience and perinatal mortality was found for nurse‐midwives. Midwife‐only trained LMCs could require additional training and/or supervision in their first year of practice.